Hydrolagus erithacus sp. nov. (Chimaeriformes: Chimaeridae), a new species of chimaerid from the southeastern Atlantic and southwestern Indian oceans - Walovich, Kristin A.; Ebert, David A.; Kemper, Jenny M. (Zootaxa, 2017)
A new species of chimaerid, Hydrolagus erithacus sp. nov., is described from nine specimens collected from the southeast Atlantic and southwest Indian oceans from depths of 470–1,000 meters. This species is distinguished from all other Hydrolagus species based on the following characteristics: head bulky, relatively large, followed by stocky body; head and body height from about pectoral fin origin to pelvic fin origin similar, then tapering rapidly to filamentous tail; first dorsal fin spine height about equal to, or slightly less than first dorsal fin apex height; second dorsal fin up to 81% of total body length and uniform in height; trifurcate claspers forked for approximately 20% of total length; robust frontal tenaculum nearly uniform in width, prepelvic tenaculae with five to seven medial spines, and a uniform black coloration with robust, non-deciduous skin. Comparison of mitochondrial NADH2 gene sequences with other morphologically similar Hydrolagus species suggests that H. erithacus is a distinct species.